Finanças comportamentais e o estudo de reações no mercado de capitais através de modelos baseados em agentes - Faria, Paulo Roberto Domingues de (2010)
Market efficiency and rationality of economic agents are among the main subjects for debate in the area of Finance. With the development of the field of study of Behavioral Finance some serious works have been developed to improve the financial models with the incorporation of social and psychological elements to the financial theory. This paper presents some of the assumptions of the modern theory of finance and the main ideas of behavioral finance. It also presents empirical research involving the simulation of heterogeneous agents in an artificial stock market. The objective is to evaluate if the interaction of these agents can impact the behavior of asset prices in a different way from that expected by the traditional finance theories.